2011
DOI: 10.1002/pola.24859
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and computational modeling of benzodithiophene donor–acceptor semiconducting polymers

Abstract: Donor-acceptor semiconducting polymers containing benzodithiophene with decyl phenylethynyl substituents have been synthesized. Density functional calculations on the polymers' band gaps and frontier orbitals energies provide reasonable agreement with cyclic voltammetry, photoelectron spectroscopy, and UV-vis absorption measurements. V C 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…[ 25 ] Benzobisthiadiazole is a strong acceptor and generated donor-acceptor polymers with low bandgap. [ 25 ] …”
Section: Donor-acceptor Alternating Copolymers Of 48-dialkoxy Benzo[mentioning
confidence: 99%
“…[ 25 ] Benzobisthiadiazole is a strong acceptor and generated donor-acceptor polymers with low bandgap. [ 25 ] …”
Section: Donor-acceptor Alternating Copolymers Of 48-dialkoxy Benzo[mentioning
confidence: 99%
“…However, the HOMO was relatively unchanged and the change in the bandgap was due to the change in the LUMO of the synthesized D-A copolymers. 115 Among these polymers the lowest bandgap of 1eV was measured for 55d with benzobisthiadiazole as the acceptor unit. 115 Cho et al reported BDT D-A copolymers 56a-56b…”
mentioning
confidence: 99%
“…115 Among these polymers the lowest bandgap of 1eV was measured for 55d with benzobisthiadiazole as the acceptor unit. 115 Cho et al reported BDT D-A copolymers 56a-56b…”
mentioning
confidence: 99%
See 2 more Smart Citations